Comparison of Pyridazinium Electro-oxidation on Boron-doped Diamond (BDD) and SnO2 in a Basic Medium - Bouya,H. (2015)
The eco-friendly ionic liquid 1-(2-ethoxy-2-oxoethyl) pyridazinium chloride's (EOPC) newly synthesised electro-oxidation behaviors of boron-doped diamond (BDD) and SnO2 in an alkaline media were compared using galvanostatic electrolysis. Various pyridazinium and alkaline concentrations were studied. In addition, the temperature, and density current effect of pyridazinium oxidation were investigated. The BDD showed a higher activity toward pyridazinium oxidation than the SnO2. This is mainly due to the higher characteristics and the relatively inert nature of the BDD. The bulk electrolysis tests have shown that the complete removal of COD can only be achieved using a boron-doped diamond and that SnO2 only permits a partial oxidation of pyridazinium. On the basis of the chemical oxygen demand (COD) evolution released during the treatment, a total mineralization has been proposed. Finally, electrolysis has been performed in the presence of NaCl. Based on these results, it is concluded that BDD has less poisoning effects and higher activity than SnO2 for the selective electro-oxidation of pyridazinium.